PENENTUAN UMUR SIMPAN TORTILLA DENGAN METODE AKSELERASI BERDASARKAN KADAR AIR KRITIS SERTA PEMODELAN KETEPATAN SORPSI ISOTHERMINYA [Shelf Life Study of Tortilla Using Accelerated Shelf Life Testing (ASLT) Method and its Mathematical Modeling of Moisture S - Slamet Budijanto; Azis Boing Sitanggang; Yuni Dwi Kartika (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2010)
Accelerated shelf life testing (ASLT) method was used to determine the shelf life of tortilla chips based on critical moisture content approach. Crispiness was found to be the critical parameter in tortilla chips deterioation. The curve of moisture sorption isotherm was resulted by plotting water activity values (aw) and equilibrium moisture contents (Me) using eight salts with RH values at range of 11.3-90.3%. There were five models of sorption isotherm tested, namely Hasley, Chen-Clayton, Henderson, Caurie, dan Oswin model. Conclusively, Oswin model was the suitable one to depict the sorptions isotherm phenomenon in tortilla chips with MRD value of 2.33. By gathering all variables to be used in Labuza’s equation, the shelf life of tortilla chips at 38oC and 70% of RH was about 56 days.